Managing university intellectual property in the public interest Lessons from a Generation of Experience, Research, and Dialogue ; Board on Science, Technology, and Economic Policy ; Committee on Science, Technology, and Law ; Policy and Global Affairs ; Stephen A. Merrill and Anne-Marie Mazza, editors ; National Research Council of the National Academies. - Merrill, Stephen A.; Mazza, Anne-Marie (National Research Council, National Academy Press, 2011)
Thirty years ago federal policy underwent a major change through the Bayh-Dole Act of 1980, which fostered greater uniformity in the way research agencies treat inventions arising from the work they sponsor. Before the Act, if government agencies funded university research, the funding agency retained ownership of the knowledge and technologies that resulted. However, very little federally funded research was actually commercialized. As a result of the Act's passage, patenting and licensing activity from such research has accelerated. Although the system created by the Act has remained stable, it has generated debate about whether it might impede other forms of knowledge transfer. Concerns have also arisen that universities might prioritize commercialization at the expense of their traditional mission to pursue fundamental knowledge--for example, by steering research away from curiosity-driven topics toward applications that could yield financial returns. To address these concerns, the National Research Council convened a committee of experts from universities, industry, foundations, and similar organizations, as well as scholars of the subject, to review experience and evidence of the technology transfer system's effects and to recommend improvements. The present volume summarizes the committee's principal findings and recommendations.